Assessment of heavy metal and metalloid levels and screening potential of tropical plant species for phytoremediation in Singapore. (15th February 2022) - Wang, Yamin; Tan, Swee Ngin; Mohd Yusof, Mohamed Lokman; Ghosh, Subhadip; Lam, Yeng Ming
Abstract: Heavy metal or metalloid contamination is a common problem in soils of urban environments. Their introduction can be due to unpremeditated anthropogenic activities like atmospheric deposition produced by diffuse sources, construction activities and landscape maintenance. Phytoremediation is a rapidly evolving, sustainable approach to remediate the contaminated lands where metals and metalloids are highly persistent in the environment. The present work sets out to determine the level of 12 heavy metals and metalloids (As, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sb and Zn) in soil and their accumulation by plant foliage found in nature parks and industrial sites in Singapore. The latter also involve the investigation of the remediation capacity of selected tropical plant species found at the sampling sites. The study is done using digestion and inductively coupled plasma-optical emission spectrometry. Eleven soil sampling sites across Singapore with 300 sampling points were selected, where soil (0–10 cm) and plant foliage samples were collected. Bioconcentration factors were determined to assess the phytoremediation potential of the collected plant species. Toxicity risk of heavy metals were assessed by comparing the target and intervention values from the soil quality guidelines by the Dutch Standard. Results of the study revealed there were regions where levels of heavy metals and metalloids were relatively high and could affect the environment and the health of flora and fauna in Singapore. Our study discovered that there were available tropical plant species (e.g., wildflowers, ferns and shrubs) which could potentially play a significant role in the remediation of contaminated lands that could open up a huge possibility of developing a sustainable and environmentally-friendly way of managing this emerging urban problem. Results showed that 12 plant species, including hyperaccumulator like Pteris vittata, Centella asiatica, were effective for the accumulation of heavy metals and metalloids. Highlights: Assessment of heavy metal and metalloid pollution in urban soils in Singapore. Monitoring plant species' efficiency in phytoremediation by island wide survey. 12 tropical plant species with phytoremediation potential have been identified.